Cortical and spinal excitabilities are differently balanced in power athletes. Issue 3 (15th March 2020) - Grosprêtre, Sidney; Bouguetoch, Amandine; Martin, Alain
Abstract: It is recognised that power-sport practices have a particular effect on lower-limb neuromuscular parameters. Less is known about corticospinal network adaptation, however, or whether these adaptations are specific to the lower limb. In the present study, the corticospinal and spinal excitabilities of upper and lower limbs have been examined in a group of untrained participants (UT, n = 10) and compared to those of a group of well-trained athletes practicing parkour (PK, n = 10). This activity, consisting of overcoming obstacles offered by the urban environment, was chosen as a model of power activity. The motor evoked potentials (MEPs) induced by transcranial magnetic stimulations and H-reflexes and maximal M-waves evoked by peripheral nerve stimulations were elicited in both upper- (flexor carpi radialis [FCR]) and lower-limb muscles (soleus [SOL] and gastrocnemius medialis [GM]). The results tended toward an overall greater corticospinal excitability in PK than in UT (as evidenced by greater MEP/Mmax ratio) and lower spinal excitability (lower Hmax/Mmax). H/MMAX ratio was lower for PK (0.32) than for UT (0.41) in SOL ( p = 0.02), while MEP/MMAX was greater for PK than for UT in FCR (PK: 0.12; UT: 0.06; P = 0.04) and in GM (PK: 0.05, UT: 0.03, P = 0.02). In both limbs, the decrease of spinal excitability induced by parkour practice was counterbalanced by an increase in cortical excitability. Finally, the present study indicates that such long-term power practice leads to similar corticospinal plasticity in upper and lower limbs, explained by the similar solicitation of those muscles.